2015
DOI: 10.7150/jca.10879
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Acidosis Promotes Mitochondrial Apoptosis Pathway: Role of EMMPRIN Down-regulation via Specific Single-chain Fv Intrabody

Abstract: Extracellular matrix metalloproteinase inducer (EMMPRIN) is a human leukocyte surface molecule that is enriched on the surface of many cancer cells, and it plays an important role in proliferation and metastasis. In this study, we utilized the chimeric adenoviral vector Ad5/F35 carrying gene encoding scFv against EMMPRIN (scFv-M6-1B9) to down-regulate EMMPRIN cell surface expression and investigated programmed cell death response in colorectal cancer (CRC) cell, Caco-2. The scFv-M6-1B9 intrabody exhibits robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Interestingly, inhibition of EMMPRIN via RNA interference has been found to induce apoptosis in both solid tumour cells and haematologically malignant cells. 41,45,46 Additionally, a role of EMMPRIN in autophagic cell death has been reported. 47,48 Therefore, by downregulating EMMPRIN, icaritin might exert an anti-tumour effect by targeting multiple steps in tumour progression, including promoting apoptosis, inducing autophagy and suppressing invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, inhibition of EMMPRIN via RNA interference has been found to induce apoptosis in both solid tumour cells and haematologically malignant cells. 41,45,46 Additionally, a role of EMMPRIN in autophagic cell death has been reported. 47,48 Therefore, by downregulating EMMPRIN, icaritin might exert an anti-tumour effect by targeting multiple steps in tumour progression, including promoting apoptosis, inducing autophagy and suppressing invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these previous studies, evidence from the present study also showed that icaritin suppressed the invasive potential of GBM cells by downregulating EMMPRIN expression, supporting the role of EMMPRIN as novel target for suppressing GBM invasion. Interestingly, inhibition of EMMPRIN via RNA interference has been found to induce apoptosis in both solid tumour cells and haematologically malignant cells . Additionally, a role of EMMPRIN in autophagic cell death has been reported .…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic stimuli, including cancer chemotherapies, are capable of inducing intracellular acidification (29). Direct induction of an acidic pHi reportedly triggers the classic hallmarks of apoptosis, including nuclear condensation, cytoplasmic vacuolization and endonuclease-mediated DNA degradation (30). These observations suggest a direct association between acidification and a decrease in the viability of colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The retention of a particular integrin subunit in the ER by an intrabody allowed study of how integrin heterodimers form and revealed a hierarchy in complex formation when different subunits combine [280]. Tumour invasion and metastasis were further targeted using an intrabody to block the activation of matrix metalloproteinases in an in vitro model [281,282]. Plasma membrane extensions that also have proteolytic activity, called invadopodia, allow cancer cells to invade their surroundings and form metastases.…”
Section: Applications In Oncology: Targeting At the Tissue Levelmentioning
confidence: 99%